UNRAVELING THE NEXUS OF BLOCKCHAIN TECHNOLOGY ANDFINANCIAL SERVICES: A MULTI-DIMENSIONAL LITERATURE SYNTHESIS - Gatot Dwiyono; Nenden Hendayani; Edi Tedi (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Blockchain technology has emerged as a transformative disruptor in the financial services realm. This research undertakes an extensive review of academic literature to comprehensively explore the intricate interplay between blockchain technology and financial services. Drawing from diverse scholarly sources, the synthesis probes various facets of this relationship, encompassing the fundamental tenets of blockchain, its applications within financial services, associated benefits, challenges, empirical substantiation, and forthcoming trends. The synthesis illuminates blockchain's potential to overhaul conventional financial systems by furnishing heightened security, transparency, and operational efficiency, facilitating broader financial inclusivity. Nevertheless, notable hurdles such as scalability, regulatory ambiguities, and privacy apprehensions must be surmounted to ensure widespread adoption. Furthermore, the synthesis sheds light on emerging paradigms, such as the convergence of blockchain with nascent technologies and the ascent of decentralized finance (DeFi) platforms, which herald promising avenues for subsequent research endeavors and practical implementations. Ultimately, this literature synthesis furnishes actionable insights for industry practitioners, policymakers, and researchers alike, furnishing them with the requisite guidance to navigate strategic decisions and propel the continual evolution of blockchain technology within financial services.